STRATEGI PENINGKATAN KUALITAS PRODUK BODY SCRUB PT BALI TANGI DENGAN METODE QUALITY FUNCTION DEPLOYMENT - Triastuti, Ni Ketut Titi; Wiranatha, A.A.P. Agung Suyawan; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): DesemberDO - 10.24843/JRMA.2018.v06.i04.p11, 2018)
The purposes of this research were to find out the attributes of customer importance, to measure the level of customer satisfaction and to find out the strategy in improving the product quality of PT. Bali Tangi’s Body Scrub. The Quality Function Deployment (QFD) was used to gain customer’s perception and building the house of quality. The results of this study indicate that the attributes of customer importance are the information on packaging, product’s safety, product’s benefits, product’s contents, product’s hygiene, product’s certification, product’s aroma, shelf life product, packaging’s form, product’s dose, packaging’s color, product’s form and product’s color. The customer satisfaction levels are satisfaction and quite satisfaction. The attributes of product with satisfaction are obtained in attribute of information on packaging, product’s safety, product’s benefits, product’s contents, product’s hygiene, product’s certification, product’s aroma, shelf life product, packaging’s form, product’s dose, packaging’s color and product’s color. The attributes of product with quite satisfaction is obtained in the product’s form. The strategy in improving the product quality that can be recommended are the company need to evaluate the attributes of customer importance and technical parameters to reach the company’s target. The priority attributes are the product’s form with an improvement ratio of 1.47 and the determination of materials formulation with a technical importance level of 452.00. Keywords : Quality Function Deployment, Body Scrub.